Faktor-faktor yang berhubungan dengan kejadian ISPA Pada Anak Usia 6-11 Tahun Di Puskesmas Kahakitang Kab. Kepulauan Sangihe - Ivanna N. Takalihiang; Kristine Dareda; Sri Wahyuni (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2023)
Acute respiratory infections (ARI) is the main cause of morbidity and mortality from infection diase in the world. The purpose of this research was to find out the factors contributing to the incidence of ARI (acute respiratory infection) in children aged 6-11 years at the kahakitang public health center, Sangihe Island District. This research used an analytic descriptive method which is cross sectional. Sampels were taken based on the number of respodents as many as 36 people using purposive sampling. Data collection was done by giving qustionnaires and observation sheets. Furthermore, the data was processed by running the SPSS computer program version 16,0 to be analyzed by chi-square statstic test. The research findings indicate that there is no significant relationship between immunization and the incidence of Acute Respiratory Infections (ISPA) with a p-value of 0.098. This p-value is greater than the significance level (a) of 0.05. However, there is a significant relationship between behavioral factors and the incidence of ISPA (p = 0.000), and also a significant relationship between environmental factors and the incidence of ISPA (p = 0.033). Both of these p-values are smaller than the significance level of 0.05. In conclusion, there is no significant relationship between immunization and the incidence of ISPA in children aged 6-11 years at the Kahakitang Public Health Center, Kabupaten Kepulauan Sangihe. However, there is a significant relationship between behavioral and environmental factors and the incidence of ISPA in children aged 6-11 years at the same health center. It is recommended to increase awareness about the importance of immunization for children's immune system and to promote clean and healthy lifestyles, along with an active role in maintaining environmental hygiene.